TRANSFORMASI PELAYANAN DESA BERBASIS DIGITAL MODERN DAN PENGEMBANGAN SUMBER DAYA MANUSIA MELALUI PROGRAM PELATIHAN - Jatmika, Andy Hidayat; Muziburrahman, Ilham; Wati, Putri Bima; Dwiyanti, Putri; Hadiningrum, Diah Sunasti; Ainun, Ainun; Metamelya, Baiq Areta; Saputri, Hartini; R, Rifqi Januar Islami; Naim, Syahrul; Nizan, Afnan (Jurnal Wicara, 2023)
Mataram University as a tertiary institution has the duties and functions of implementing the Tri Dharma of Higher Education, namely education and teaching, research, and community service. Such efforts are not only carried out and become the obligation of lecturers alone, but also for students. The use of technology in the village of North Surabaya is still lacking, the village administration system is still carried out manually and the dissemination of village information is still uneven. With the existence of a village website, it is hoped that administrative management and distribution of information will be evenly distributed. The understanding of the North Surabaya village community about digital is still very minimal, of course there must be efforts that needs to be done to increase human resources regarding digitization in order to take advantage of the potential that exists in the village of North Surabaya. The implementation of the work program is carried out using a participatory method by collaborating with various existing stakeholders, the output of the real work lecture program is assisting SSID development, making a Local Area Network (LAN) master plan, and creating a temporary village website in the village of North Surabaya. For 45 days in North Surabaya Village we have carried out the main program, namely creating a temporary website containing village infographics and making a LAN master plan which later the village can use as a reference when installing a LAN network at the village office. In addition to the main work program, there is also an additional work program, namely the socialization of "Cute Internet" with the aim of developing human resources in North Surabaya Village to make positive use of the internet.